Changing nature of adoption and need for post-adoption services: Intercountry adoption practice in Taiwan and Australia. (May 2023) - Lin, Ching-Hsuan; Chen, Yu-Wen; Wang, Chin-Wan; Wright, Amy Conley; Spencer, Margaret; Van Wichelen, Sonja
This study explores issues on post-adoption services in intercountry adoptions based on the perspectives of adoption professionals from Taiwan and Australia. Findings revealed that both birth and adoptive families identify service needs for material and emotional support and connection after the adoption process is finalized. However, the current lack of government funding for post-adoption services result in gaps in service delivery. Adoption agencies experience challenges in funding and balancing the interests of the child and the two families. Implications for practice and policy are discussed to enhance the quality of post-adoption services and improve the well-being of the adoption triad.